Synthesis and Magnetic Properties of a New Family of Macrocyclic M(3)(II)Ln(III) Complexes: Insights into the Effect of Subtle Chemical Modification on Single-Molecule Magnet Behavior - Feltham, Humphrey LC (AMER CHEMICAL SOC, 2022)
10.1021/ic300819u